Italy - Bonetto, Cristian; Blasi, Abigail; Christiani, kerry; #aClark, Gregor; Dixon, Belinda; Garwood, Duncan; hardy, Paula; Sainsbury, Brendan; Williams, Nicola (Lonely Planet guidebooks., 2016)
Recommends restaurants, accommodations, attractions, shopping, and entertainment; and provides information on transportation and planning itineraries.